Análise do comportamento de um módulo FV sujeito à ondulação de corrente de alta frequência - Sales Júnior, Ildenor David (2023)
The specific aim of this work is to analyze the behavior of photovoltaic (PV) modules when connected to high-frequency switched circuits, with the aim of reducing current ripple. The relationship between current ripple at the output of the photovoltaic module will be investigated, and the appropriate sizing of the filter capacitor used between the module and the connected circuit will be determined. The use of a filter capacitor can simplify the process of reducing current ripple and replace the need for complex implementations in converter circuits. Thus, appropriate sizing of the filter capacitor is a more economical and efficient solution to achieve this goal. Considering the objective of this study, an approximate photovoltaic electrical model was proposed to simplify the analysis and incorporate the dynamic characteristics of the module. The model was evaluated for an operating point close to the maximum power point (MPP). The filter capacitance calculation methodology can be applied to different operating temperatures and equivalent series resistance values of the capacitor to identify the worst-case scenario of operation. A prototype was developed to evaluate and validate the proposed methodology. The prototype was applied to a 210 W PV module and a load switched by a MOSFET at a frequency of 50 kHz. Comparison between the calculation, simulation, and experimental results was performed through the evaluation of the Fourier series and the fundamental frequency of the circuit, which proved satisfactory for the purpose of this work.